2023
DOI: 10.1038/s41598-023-38708-3
|View full text |Cite
|
Sign up to set email alerts
|

Intact predictive processing in autistic adults: evidence from statistical learning

Abstract: Impairment in predictive processes gained a lot of attention in recent years as an explanation for autistic symptoms. However, empirical evidence does not always underpin this framework. Thus, it is unclear what aspects of predictive processing are affected in autism spectrum disorder. In this study, we tested autistic adults on a task in which participants acquire probability-based regularities (that is, a statistical learning task). Twenty neurotypical and 22 autistic adults learned a probabilistic, temporal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
3
6
0
Order By: Relevance
“…Contradictory to our expectations, we did not find evidence in favor of altered dynamics of statistical learning in autism (which would have been indicated by a significant learning phase and group interaction). Research has shown that statistical learning (Brown et al, 2010;Foti et al, 2015;Fucà et al, 2021;Izadi-Najafabadi et al, 2015;Nemeth et al, 2010;Obeid et al, 2016;Pesthy et al, 2023;Treves et al, 2023) and consolidation (Nemeth et al, 2010) are intact in autism, and here, we did not observe significant differences between the groups regarding underlying mechanisms of learning.…”
Section: Discussion Of Studysupporting
confidence: 44%
See 4 more Smart Citations
“…Contradictory to our expectations, we did not find evidence in favor of altered dynamics of statistical learning in autism (which would have been indicated by a significant learning phase and group interaction). Research has shown that statistical learning (Brown et al, 2010;Foti et al, 2015;Fucà et al, 2021;Izadi-Najafabadi et al, 2015;Nemeth et al, 2010;Obeid et al, 2016;Pesthy et al, 2023;Treves et al, 2023) and consolidation (Nemeth et al, 2010) are intact in autism, and here, we did not observe significant differences between the groups regarding underlying mechanisms of learning.…”
Section: Discussion Of Studysupporting
confidence: 44%
“…Before assessing our main research question, we tested statistical learning employing the methods of the original article (Pesthy et al, 2023), using our own data quality control measures. This showed that participants successfully learnt the statistical characteristics of the task and there were no differences in the groups' performance.…”
Section: Results Of Studymentioning
confidence: 99%
See 3 more Smart Citations